Locality, regeneration & divers[c]ities - Bennett, Sarah; Butler, John (John H.) (Advances in art & urban futures, 2000)
As British cities lose the cultural connections with their industrial past, many seek to build new postindustrial futures through urban regeneration. Art projects play a key role in policymaking that aims to regenerate neglected neighbourhoods. This study focuses particularly on the ways in which newlydeveloped cultural institutions tend to be flagships for regeneration the Tate Modern in Southwark is one such example.